ISOLATION AND TEST OF HETEROTROF BACTERIA ACTIVITY TO PATHOGEN BACTERIA FROM SEA DISTRICT SIAK REGENCY, RIAU PROVINCE - Rendy Lani Dinata; Feliatra Feliatra; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT  Heterotrophic bacteria are bacteria that require organic carbon and inorganic nitrogen as an energy source, Research aims to determine the number of heterotrophic bacteria, knowing the results of its activity test against pathogenic bacteria (Vibrio sp, Aeromonas sp, Pseudomonas sp) and to know the species of heterotrophic bacteria through DNA test isolated from estuari waters of 15 ppt and the industrial estuary at coastal areas Sungai Kayu Ara  village with salinity 27 ppt, Siak District. Distribution of bacteria at station  higher than station 2 with value of nilai 7,04 x 107cfu / ml at station 1 to 6,46 x 107cfu / ml at station 2. Furthermore, through simple linear regression test known that the growth of heterotrophic bacteria on environmental parameters (DO, pH, temperature and salinity) categorized very weakly with the value of r = 0.10 in all parameters. Based on the antagonism test on pathogenic bacteria, it was found that there were 9 bacterial isolates that potentially inhibited the growth of the three pathogenic bacteria, namely: RM3, RM4, RM5, RM6, RM8, RM11, RL15, RL17 and RL 24 with inhibit zone ranges from 0.6 - 18mm, where the RM11 (12-15.3 mm) isolate as the best isolate in its inhibitory properties. By DNA test with 16S rRNA method and BLAST analysis, it was found that Bacillus safensis, Alcaligenes faecalis, Enterobacter sp, Enterococcus sp and Vagococcus sp species were identified as unidentified and possibly non-registered species in Genbank NCBI because it has a homology percentage of only 84%.                                                      Keywords: Heterotrophic Bacteria, Distribution, Antagonism, DNA